Etta Invincible - Eschmann, Reese (Aladdin, 2022)
Etta Johnson, twelve, has Loud Days and Quiet Days, and is trying to come to terms with her apparently increasing hearing loss. To cope, she retreats into her work on her comic book, Invincible Girl, about a girl who is unstoppable, brave, daring, and bold. When she and her new classmate and friend, Eleazar, discover a magical train and Eleazar's dog disappears on it, Etta and he board the train, full of magic and riddles to solve, to rescue the dog and, in the end, themselves.